Craniosynostosis is a feature of Costello syndrome. Issue 4 (28th December 2021) - Weaver, K. Nicole; Care, Marguerite; Wakefield, Emily; Zarate, Yuri A.; Skoch, Jesse; Gripp, Karen W.; Prada, Carlos E.
Abstract: Costello syndrome (CS) is an autosomal dominant disorder caused by pathogenic variants in HRAS . Craniosynostosis is a known feature of other RASopathies (Noonan and cardiofaciocutaneous syndromes) but not CS. We describe four individuals with CS and craniosynostosis and present a summary of all previously reported individuals with craniosynostosis and RASopathy.